Role of Ayurvedic Panchakarma Treatment in Male Infertility (Severe Oligoasthenozoospermia) - Mehedi Hasan, Dr. Md.; Fazlul Kabir, Dr. Md.; Khandaker, Dr. Md. Alahi; Ramavani, Dr. Morusupalli; Akter, Dr. Mahmuda (Clinical Medicine And Health Research Journal, 2023)
Infertility is one of the global burning issues which affects the couple socially and individually in a negative way. There are numerous etiological factors that play a significant role to it e.g. like hormonal variations, structural abnormality, functional disorders, psychological factors etc. In Ayurveda a separate department (Tantra) known as sexual invigoration (Vajeekarana) is mentioned by Charak Samhita and Sushrut Samhita to address this problem. The study patient reported with oligozoospermia (low sperm count) and Asthenozoospermia (low sperm motility). Where medicinal treatment (shaman chikitsa) and purification therapy (shodhana chikitsa) i.e. panchakarma especially Intra Urethral Uttar Basti (IUUB) is the management. After 4 months of treatment, his condition is improved from severe oligoasthenozoospermia to normozoospermia. Ayurvedic Panchakarma treatment is safe and effective approach for oligoasthenozoospermia.